Pengaruh model pembelajaran conceptual understanding procedures berbantuan media papan putaran terhadap kemampuan pemahaman konsep siswa kelas V sekolah dasar - Lailasari, Afifah Nur; Rini, Zulmi Roestika (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to determine the influence of the Conceptual Understanding Procedures Learning Model assisted by round board media on concept understanding. This type of research is Quasi Experimental Design in the form of Nonequivalent Control Group Design. The population in this study were all students at SD Negeri Langensari 01 and SD Negeri Langensari 03. The sample used was non-probability sampling with a purposive sampling technique. The sample for this research is class V 01 as the experimental class and V 03 as the control class. Data collection techniques are test and non-test techniques. Test techniques use pretest and posttest while non-test techniques use observation, questionnaires and documentation. Data analysis techniques using normality test, homogeneity test, independent sample t-test and simple linear regression. The results of the research show: (1) There is a difference in students' ability to understand concepts regarding the use of the Conceptual Understanding Procedures model assisted by round board media, with a significance value of 0.002 <0.05 (2) There is an influence of using the Conceptual Understanding Procedures learning model assisted by round board media on students' ability to understand concepts with significance values ​​of 0.001 and 0.000 < 0.05.